Synthesis optimization of 2-(4-N-[11C]methylaminophenyl)-6-hydroxybenzothiazole ([11C]PIB), β-amyloid PET imaging tracer for Alzheimer's disease diagnosis. (November 2015) - Coliva, A.; Monterisi, C.; Apollaro, A.; Gatti, D.; Penso, M.; Gianolli, L.; Perani, D.; Gilardi, M.C.; Carpinelli, A.
Abstract: [11C]PIB is the most used amyloid plaques-specific positron-emitting radiotracers. The radiosynthesis of this compound, carried out by methylation of its precursor with [11C]methyl triflate in 2-butanone, has been improved optimizing the initial concentration and the purification method. Two HPLC methods were compared: good radiochemical yields, specific activities, and chemical purity above 98% were achieved by using as eluant acetonitrile/citrate and formulation in 10% ethanol. Highlights: Good yields and specific activity of [11C]PIB were obtained by reaction parameters optimization. Improvement of the HPLC purification. Quality parameters and drug formulation allows a readily application in clinic.